PPARalpha agonists regulate lipid metabolism and nitric oxide production and prevents placental overgrowth in tern in placentas from diabetic rats - Martinez, Nora Alicia (2011)
Maternal diabetes impairs fetoplacental metabolism and growth. Peroxisome proliferator-activated receptor α (PPARα) is a nuclear receptor capable of regulating lipid metabolism and inflammatory pathways. In this study, we analyzed whether placental and fetal PPARα activation regulates lipid metabolism and nitric oxide (NO) production in term placentas from diabetic rats. Diabetes was induced by neonatal streptozotocin administration. On day 21 of pregnancy, placentas from control and diabetic rats were cultured in the presence of PPARα agonists (clofibrate and leukotriene B4 (LTB4)) for further evaluation of levels, synthesis, and peroxidation of lipids as well as NO production. Besides, on days 19, 20, and 21 of gestation, fetuses were injected with LTB4, and the placentas were explanted on day 21 of gestation for evaluation of placental weight and concentrations of placental lipids, lipoperoxides, and NO metabolites. We found that placentas from diabetic rats showed reduced PPARα concentrations. They presented no lipid overaccumulation but reduced lipid synthesis, parameters negatively regulated by PPARα activators. Lipid peroxidation and NO production, increased in placentas from diabetic rats, were negatively regulated by PPARα activators. Fetal PPARα activation in diabetic rats does not change placental lipid concentrations but reduced placental weight and NO production. In conclusion, PPARα activators regulate lipid metabolism and NO production in term placentas from diabetic rats, an activation that regulates placental growth and can partly be exerted by the developing fetus.